Integra????o regional assim??trica na Am??rica do Sul e os efeitos dos investimentos em fundos e a????es de coes??o no Mercosul - Soares, Danuta Coelho de Oliveira (2013)
The current study analyzes the process of regional integration of South America and its cohesive investments in the MERCOSUL which is marked by fierce regional assymetry which harms the evolution of economic blocks of the subcontinent, such as CAN and UNASUL, mainly, by the failed pursuit of initial objects and the inefficiency of the infrastructure, such as ports, highways, waterways, railways, bridges, power plants, and so forth. The goal of this research consists of analyzing the integration process of South America and its investments in growth and integration in MERCOSUL, through a bibliographical survey and a qualitative approach. Nevertheless, it can be observed that the mechanisms to further this integation are not enough to promote a coordinated structural as well as economic and social cohesion since the development process of integration is driven by works from IIRSA Plan, a shortage of capital programs and by state interests to the detriment of the collectives. It can currently be observed that the recovery of MERCOSUL with the approach and investment in cohesion funds such as FOCEM, notwithstanding new revitalization initiatives of the IIRSA works by UNASUL, with BNDES being a primary financier. However, the structural funds have deficiencies such as a lack of resources, lack of political-institutional convergence in the intrablock commerce, with ineffective management and protectionist measures. Aggravated by a South American intergraton process which proposes utopian goals for the creation of a common market, without regard to the establishing of basic structural conditions. Therefore, it is suggested that there be larger financial investments, improvements in the political-institutional articulation, and reduction of rivalries. These soluions will promote the correct management of resources, besides the necessity of new studies that demonstrate the potential of the region and provide solutions that promote equity of the Member-Nations through the reduction of regional assymetries.